Impacts of Recent Mill Closures and Potential Biofuels Development on Maine’s Forest Products Industry - Crandall, Mindy; Anderson, James; Rubin, Jonathan (Maine Policy Review, 2017)
The economic contributions of a sector (i.e., employment, output, value added) are a measure of how money from that sector moves about a regional economy. Using 2014 estimates of economic contributions from the forest product industry in Maine, we estimate the 2016 contribution by considering the impacts from several recent mill closures (five pulp/paper, two bioelectric). The loss of these mills, particularly paper mills, reduces the economic contributions of the forest products industry relative to the state economy and distorts markets for low-value wood. We also explore a prospective opportunity to revive low-value wood markets by modeling the economic impacts from a hypothetical colocated biorefinery, where wood chips are turned into advanced fuels and chemical coproducts. The dollar value of economic impacts from such an investment are small relative to the total industry, but they may prove significant for some rural communities.